The 12th Symposium on Polar Science, Program and Abstracts, Session OG - 奥野, 淳一; Okuno, Jun'ichi (2021)
The 12th Symposium on Polar Science, 15–18 Nov. 2021, National Institute of Polar Research (NIPR) Research Organization of Information and Systems (ROIS) conference object